SOME ECONOMIC STUDIES IN INTEGRATED CONTROL OF SPINYBOLLWORM - N. All-mallah (Mesopotamia Journal of Agriculture)
The results of the statistical analysis indicated the existence of significant difference in the mean of the percentage of loss in cotton product according to the variety of cotton used in study, The mean of this rate for the varieties Cooker and Montana significantly Exceeded the means of the other types expect the variety sp as the difference between them was not significant, while the correlation was positive and insignificant (+0,53) between the percentage of loss in cotton product and the quantity of loss in other varieties of cotton, The date of planting did not have a responsible effect on the general mean of the quantity of loss in cotton product, The mean of the percentage o loss for the correlation of fertilizing with other minor elements was significantly more than all the mean of the other treatments expect fertilizing treatment with minor elements and spraying with leaf fertilizer. The value of economic threshold reached 2,51 – 2,85 larva/plant on purchasing insecticides for commercial prices, while it ranged between 2,05 - -2,15 larva/plant on purchasing insecticides for official prices. Concerning the effect of field treatment with insecticides (Confidor, Medamec, Endosulfan) on the quantity of cotton Al-zahr yield, the study indicated that the product of one-dounm of the cotton in the piece of land treated with insecticides reached 1290,84Kg/donum, while this production reached 818,92kg/donum in the piece of land not treated with insecticides. The production mean of one plant of Al-zahr cotton in the first harvesting in Al-Rasheediyyah reached 77,22 gram, 71,76, 71,66, 116,11, 115,92, 85,51gram/plant for the variety Cooker, Lashata, Montana and Dunn 1047, strain B, sp successively,The study also indicated that treating cotton seeds of Lashata variety with Cruiser insecticide led to an increase in the yield of Al-zahr cotton (138,88 gram/plant).